(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the nursing consultancy mediated by messaging applications for the breastfeeding process up to 04 months of life. Method: Quantitative, longitudinal study with 57 lactating women, comprising: 1) Face-to-face nursing consultation at the maternity 2) Subsequent nursing consultations, mediated by a messaging application. After the consultation at the maternity ward, the participants were randomly divided into two groups: the control group, in which a new contact was made at the end of the research, in the 4th month, and the intervention group that was followed up in the 2nd, 7th and 15th day after hospital discharge and then monthly until the 4th month. Results: The socio-gestational profile of the participants between the groups was homogeneous, except for parity (p 0.026). 96.7% of the participants called themselves brown/black. All participants underwent prenatal care, however, in the CG 46.7% reported not having received guidance on breastfeeding during prenatal care and in the IG 55.6%. Both in the CG and in the GI, the lactating women presented difficulties during the breastfeeding process: difficulties in latching on, the baby’s position for breastfeeding, crying after breastfeeding, among others. Conclusion: It can be concluded that health education actions through dialogue between users and professionals, with the aid of technologies, especially consulting via message and/or audio by application, can allow the provision of care and access to information more quickly and thus enable the construction of collective knowledge, which brings contributions to the promotion of breastfeeding.